Genome-wide dynamics of replication timing revealed by in vitro models of mouse embryogenesis - Hiratani, Ichiro; Ryba, Tyrone; Itoh, Mari; Rathjen, Joy; Kulik, Michael; Papp, Bernadett; Fussner, Eden; Bazett-Jones, David P.; Plath, Kathrin; Dalton, Stephen; Rathjen, Peter D.; Gilbert, David M. (Genome Research, 2010)
Differentiation of mouse embryonic stem cells (mESCs) is accompanied by changes in replication timing. To explore the relationship between replication timing and cell fate transitions, we constructed genome-wide replication-timing profiles of 22 independent mouse cell lines representing 10 stages of early mouse development, and transcription profiles for seven of these stages. Replication profiles were cell-type specific, with 45% of the genome exhibiting significant changes at some point during development that were generally coordinated with changes in transcription. Comparison of early and late epiblast cell culture models revealed a set of early-to-late replication switches completed at a stage equivalent to the post-implantation epiblast, prior to germ layer specification and down-regulation of key pluripotency transcription factors [POU5F1 (also known as OCT4)/NANOG/SOX2] and coinciding with the emergence of compact chromatin near the nuclear periphery. These changes were maintained in all subsequent lineages (lineage-independent) and involved a group of irreversibly down-regulated genes, at least some of which were repositioned closer to the nuclear periphery. Importantly, many genomic regions of partially reprogrammed induced pluripotent stem cells (piPSCs) failed to re-establish ESC-specific replication-timing and transcription programs. These regions were enriched for lineage-independent early-to-late changes, which in female cells included the inactive X chromosome. Together, these results constitute a comprehensive “fate map” of replication-timing changes during early mouse development. Moreover, they support a model in which a distinct set of replication domains undergoes a form of “autosomal Lyonization” in the epiblast that is difficult to reprogram and coincides with an epigenetic commitment to differentiation prior to germ layer specification.
10.1101/gr.099796.109